MYPES CONCENTRATION AND ITS IMPACT ON ECONOMIC GROWTH - Gomero Gonzales, Nicko Alberto (2015)
Naturally, companies seek profitable operations; to this end, they pursue economic spaces that ensure market leading, costs reduction, technological adaptation, means that lead to enhance their competitiveness and ensure its sustainability. Based on this criterion, MYPES show a preference for location in metropo-litan areas, especially Lima and Callao region, which include an average of 51.0 % of micro and small en-terprises in contrast to the formal mountain economic fringe, that gathers 21.4% of these organization, an amount aggravated when we observe that the number of the forest companies where the concentration is only 6.2% of the business conglomeration. These re-sults will be reflected in the quality of life of the popula-tion, which was one of the goals of the research, where a close relationship among economic performance, the product of the actions of the companies and of quality of life indicators. Under this criterion we state that, where fewer companies exist, such as micro and small enterprises, the greater the probability of falling into social imbalances.